2022
DOI: 10.1093/ofid/ofac309
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Simultaneous Infections With Nontuberculous Mycobacteria in the Setting of GATA2 Mutation and Myelodysplastic Syndrome

Abstract: GATA2 mutation can result in profoundly reduced monocytes, dendritic cells, NK cells, and B cells, and is associated with a predisposition for recurrent and disseminated non-tuberculosis mycobacterial (NTM) infections and myelodysplasias. Herein, we describe a unique case of three simultaneous disseminated NTM infections in a patient with GATA2 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…PVs in GATA2 can be either germline or somatic. Germline PVs follow an autosomal dominant inheritance pattern, and their clinical manifestations typically have a familiar predisposition, although the majority of germline PVs in GATA2 are de novo and not inherited 3,21 . Somatic GATA2 PVs are poorly described, and less than 4% of sporadic myeloid malignancies have somatic GATA2 PVs 11 .…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…PVs in GATA2 can be either germline or somatic. Germline PVs follow an autosomal dominant inheritance pattern, and their clinical manifestations typically have a familiar predisposition, although the majority of germline PVs in GATA2 are de novo and not inherited 3,21 . Somatic GATA2 PVs are poorly described, and less than 4% of sporadic myeloid malignancies have somatic GATA2 PVs 11 .…”
Section: Case Discussion and Review Of The Literaturementioning
confidence: 99%
“…Germline PVs follow an autosomal dominant inheritance pattern, and their clinical manifestations typically have a familiar predisposition, although the majority of germline PVs in GATA2 are de novo and not inherited. 3,21 Somatic GATA2 PVs are poorly described, and less than 4% of sporadic myeloid malignancies have somatic GATA2 PVs. 11 A previous study from our institution showed that myeloid malignancies with somatic GATA2 PVs can also demonstrate diverse immunodeficiency phenotypes, similar to patients with germline GATA2 PVs.…”
Section: A S E Discussion and Re Vie W Of The Liter Aturementioning
confidence: 99%
See 2 more Smart Citations